MANNAN TURGANBAYEV AND THE NEWSPAPER «KAZAK TILI» (Journal of history, 2022)
The purpose of this article is to pay special attention to the history of the Kazakh press. In particular, to take into account the significant contribution of the first editor-in-chief of the Kazakh Tili newspaper Mannan Turganbaev, which was published in Semipalatinsk from 1919 to 1928. Articles by Mannan Turganbaev on socio-political, socio-economic, cultural and literary topics published in the Kazakh Tili newspaper were introduced into scientific circulation and studied. It has been established that the newspaper «Kazakh Tili» was first published by the printing house «Alashorda» («Zhardem») in Semipalatinsk (Alash) from December 1919 to 1922 as an organ of the Semipalatinsk Provincial Revolutionary Committee.From the end of February 1922 to March 17, 1928, the publication was published by the Semipalatinsk regional publishing house. In general, the history of the Kazakh Tili newspaper and its role in the social and cultural life of Kazakhstan have been studied in detail on the basis of newspaper publications, archival documents, scientific articles, and press materials. Thus, the editorial role of Mannan Turganbaev in the publication and development of the Kazakh Tili newspaper was revealed. From today’s point of view, editorial and published articles by Mannan Turganbaev in the Kazakh Tili newspaper and the history of the newspaper are considered. Key words: East Kazakhstan region, Kazakh press, Kazakh culture, Kazakh society, society, politics, history.